Integrating GDS and APIs: A Hybrid Approach to Modernizing Travel Booking Systems - Jubair, Hassan (Penerbit Hellow Pustaka, 2025)
The integration of Global Distribution Systems (GDS) and Application Programming Interfaces (APIs) has the potential to transform airline ticketing and travel distribution by combining structured fare management with real-time pricing and enhanced flexibility. Traditional GDS platforms, such as Amadeus, Sabre, and Travelport, provide comprehensive access to full-service carriers (FSCs), corporate travel support, and multi-city itinerary management, but they are limited by high transaction costs, rigid booking structures, and slower fare updates. APIs, on the other hand, offer direct airline connectivity, real-time pricing, and enhanced customization, but they lack structured fare agreements and full access to FSCs. This paper explores whether a hybrid GDS-API model can address these limitations by offering cost efficiency, dynamic pricing, and broader airline coverage while integrating AI-driven automation. This study employs a systematic review, comparative analysis, and case study evaluation, focusing on platforms like Kiwi.com, eDreams ODIGEO, Traveloka, and Mystifly to assess how hybrid GDS-API integration improves pricing accuracy, ancillary service management, and operational efficiency. Additionally, the paper examines the challenges of implementation, including integration complexity, regulatory constraints, cybersecurity risks, and the initial investment required for API and AI infrastructure. Finally, future advancements in predictive analytics, blockchain-based ticketing, voice-enabled search, and New Distribution Capability (NDC) standards are discussed to determine their role in further enhancing hybrid travel platforms. This study aims to evaluate the feasibility, benefits, and potential limitations of the hybrid model, providing insights into whether it can serve as a sustainable and scalable solution for modern airline distribution.